The Factors that Influence the Language Shift among Parents - Idaryani Idaryani; Fidyati Fidyati (Universitas Pahlawan Tuanku Tambusai, 2021)
Due to the massive use of Bahasa Indonesia in the non-formal domain, it has influenced the existence of Bahasa Aceh as the heritage language among Acehnese people. This study aims to find out the factors that influence the language shift on the use of the Acehnese language as a means of communication both in written and spoken forms in non-formal domains. The study employed a descriptive qualitative method. The Data was gathered based on semi-structured interviews. The participants are 10 female parents from Lhokseumawe City, Aceh Province. The result of the study shows in term of spoken, the language shift among Acehnese parents are influenced by their level of education and negative attitude towards the Acehnese language. While in terms of written forms, the language shift among Acehnese parents is due to the efficient use of written form in the Indonesian language instead of the Acehnese language which does not yet have a standard language reference program to be used.Keywords: Parents’ Attitude, Language Shift, Heritage Language